GR_GERICHTE SR1 2023 80 vom 6. November 2024 , StGB 111-136 Leib und Leben - GR Gerichte (2024)
mehrfacher Betrug gemäss Art. 146 Abs. 1 StGB sowie Urkundenfälschung gemäss Art. 251 Ziff. 1 Abs. 1-3 StGB | StGB 137-172 Vermögen